Distribution and evaluation of bone and soft tissue tumors operated in a tertiary care center - Recep Öztürk; Şefik Murat Arıkan; Emin Kürşat Bulut; Ahmet Fevzi Kekeç; Fener Çelebi; Bedii Şafak Güngör (Acta Orthopaedica et Traumatologica Turcica, 2019)
Objective: The aim of this study was to retrospectively evaluate the patients who were operated in our orthopedics and traumatology clinic with the suspection of bone and soft tissue tumors. Methods: A total of 3133 patients (1146 (46.5%) female and 1318 (53.5%) male) who presented to our tertiary clinic from different regions of Turkey between January 2002 and July 2013 with the presumed diagnosis of bone and soft tissue tumors were analyzed according to age, gender, bone/soft tissue localization, tumoral localization, histopathological diagnosis, tumor size and incidence. Results: Of all operated patients, 2464 (78%) were diagnosed with tumor, while non-tumoral causes were found in 669 (22%) patients. Of the cases diagnosed with tumor, 1139 were bone localized, 1004 soft tissue localized, and 321 metastasis. The most common benign bone tumors were osteochondroma (130, 20%), enchondroma (96, 15%), and simple bone cysts (90, 14%), while the most common malignant bone tumors were osteosarcoma (241, 44%), ewing's sarcoma (89, 16%), and chondrosarcoma (77, 14%); respectively. The most common benign soft tissue tumors were lipoma (141, 22%), giant cell tumors (108, 16%) and ganglion (107, 16%), while the most common malignant soft tissue tumors were liposarcoma (55, 16%), synovial sarcoma (53, 16%) and malignant mesenchymal tumors (45, 13%); respectively. Conclusion: Musculoskeletal tumors are rare, but descriptive data in any region are important in order to reduce mortality and improve treatment. No significant difference was found between the data of our hospital regarding epidemiology of the musculoskeletal system tumors and those from the other regions around the world. Level of evidence: Level IV, Therapeutic study. Keywords: Epidemiological features, Epidemiology, Cancer, Turkey, Malignant tumors, Musculoskeletal tumors